The relationship between the postgraduate research climate, role clarity and research service quality: exploring the supervisors’ and students’ perceptions - Govender, Krishna K; Ramroop, Shaun (South African Journal of Higher Education, 2016)
Through surveying a sample of PG supervisors and PG research students at a large research university in SA, it was ascertained that, overall, there is little difference between the PG research students and research supervisors in terms of their perceptions, since they differed only in respect of two of the eight items used to measure their role perception (RC), and nine out of 23 items used to measure organizational climate (OC) perceptions.With respect to the overall PG research service quality (SQUAL), no significant difference was ascertained between the respondents. However, by means of structural equation modeling it was ascertained that with respect to PG research students, the OC significantly influences their perception of their role (RC), as well as their perception of the overall PG research service quality (SQUAL). In the case of the PG research supervisor, the OC only influences their perception of the SQUAL, but the results are inconclusive with regards to the association between the PG research supervisors’ RC and their perception of the SQUAL. Considering the influence of OC perceptions on the potential of research instituitons to attract and retain PG students, as well as role clarity, on the throughput of PG students,leaders of Higher Education Institutions need to be congizant of the findings in their attempt to create an OC which is research student oriented and supports research, as well as provides role clarity for both supervisors and students, and minimize any role conflict.